IMPLEMENTASI KEPUTUSAN MENTERI PENDAYAGUNAAN APARATUR NEGARA NOMOR 63 TAHUN 2003 TENTANG PEDOMAN UMUM PENYELENGGARAAN PELAYANAN PUBLIK DI PUSKESMAS ARJASA KABUPATEN SITUBONDO - Dini Noor Aini; Jefry Roby Aji Kurboyo (ACTON, 2019)
The public service sector which is a priority for service improvement and which is always demanded to improve its quality is the health service sector. The health service sector is one of the public services that must be considered quality and improved the quality of service delivery. everyone has the right to live physically and mentally, live, and get a good and healthy environment and the right to obtain health services. After knowing this condition, researchers are interested in conducting research on "Implementation of the Decree of the Minister of Administrative Reform No. 63 of 2003 Concerning Guidelines General Organization of Public Services ". The Concept of Public Service. According to the Decree of the Minister of Administrative Reforms Number 7 / M.PAN / 2/2003, that the public service provider is the government. Meanwhile, according to Law No. 25 of 2009 concerning Public Services, the definition of public services is as follows: "Public services are activities or a series of activities in the framework of meeting service needs in accordance with statutory regulations for every citizen and population of goods, services, and / or administrative services provided by service providers Data analysis The Service element gets a GOOD rating from 20 Informants, while others: 1) Service Element 1, getting an average rating ONLY, 2) Service Element 2, getting an average ADEQUATE rating, 3) Service Element 6, getting an average of GOOD AND PROFESSIONAL ratings, 4) Service Element 7, getting an average ENOUGH rating, 5) Service Element 10, getting an average rating of REASONABLE, 6) Service Element 12, get an average KADANG-KADANG SURE rating, 7) Service Element 13, getting an average ENOUGH rating. Of all service elements, 7 (seven) Service Elements have good service quality and 1 (one) service element has Good and Professional quality. Furthermore, 1 (one) service element is Average and Adequate, 1 (one) service element is fair - natural, 1 (one) service element is sometimes certain and 2 (two) service elements are sufficient. The average number of informants' answers for each service element, which rated GOOD as much as 7 (seven), ENOUGH 2 (two), GOOD and PROFESSIONAL, REGULAR, ADEQUATE, REASONABLE ONLY, and DEFINITELY SECTION, respectively 1 (one) each